Socio-Technical Perspective for Electronic Tax Information System in Tanzania - Ngowi, Lucas; Kalinga, Ellen; Mvungi, Nerey (Tanzania Journal of Engineering and Technology, 2021)
Socio-technical systems theory has rarely been used by system architects in setting up computing systems. However, the role of socio-technical concepts in computing, which is becoming social in nature, has made the concepts more relevant and commercial. Tax information systems are examples of such systems because they are influenced by external variables such as the political environment, technological trends, and social environment, introducing complexity in their deployment and determining the type of e-services and their delivery to a diverse group of people. It was observed that in Tanzania there is resistance, reluctance and minimal use of electronic tax system because of insufficient end-user support and their involvement in constructing the system. Therefore, there is need to develop an electronic tax information system using socio-technical systems perspectives to ensure design of an efficient user-friendly tax administration system. The research used the qualitative approach, featuring case studies in Korea, Chile, Tanzania, and Denmark. The study used best practices from the Organization for Economic Cooperation and Development (OECD) to benchmark Tanzania Revenue Authority current practices. It was found that tax models implemented are techno-centric push models, which don ' t attract its use by tax payers and requiring human intervention in its operation, hence not cost-effective. As the first and relevant phase in socio-technical system development, this paper presents the problem definition and analysis of e-Tax collection system in Tanzania. Keywords: Socio-technical Systems, Human Centred Design, Software Engineering, Tax Information System, Government.